Time dependent DFT investigation of the optical properties of artificial light harvesting special pairs - Agnihotri N.; Steer R.P. (My University, 2025)
Computational modeling of selected artificial special pairs has been carried out. The structures chosen are bio-inspired molecular models of the light harvesting system II that have been previously investigated experimentally. Time-dependent density functional theory calculations have been employed to characterize the inter-macrocycle interactions resulting from two zinc porphyrins that are covalently linked with rigid linkers that vary the inter-porphyrin distance and the inter-planar angle in a C2v framework. The effects of varying the linker structure have been explored for electronic states with energies up to and including the Soret-correlated states in the dimer. An expansion of the Gouterman four orbital model for the monomers to an eight orbital model in the dimers provides a reasonable explanation of the inter-macrocycle interactions and provides insight into their experimental properties. © 2016 the Owner Societies.